Observation of hearing loss in patients with chronic suppurative otitis media tubotympanic type - Maharjan, M; Kafle, P; Bista, M; Shrestha, S; Toran, KC (Kathmandu University Medical Journal, 2010)
Background: It is acknowledged that size and site of tympanic membrane perforation is proportional to degree of hearing loss but there are many studies which suggests otherwise. Persistent ear discharge is also supposed to deteriorate hearing level with passage of time. This study is carried out to find out the relation between size and site of tympanic membrane perforation and duration of ear discharge on hearing loss. Objectives: The objective of this study is to study the effect of size and site of tympanic membrane perforation and duration of ear discharge on hearing loss. Materials and methods: This is a cross-sectional prospective study conducted at Kathmandu Medical College, department of ear nose and throat from January till July 2009. One hundred patients aged between 8 to 60 years with pars-tensa perforations were included in the study. Detail clinical examination and history was carried out followed by hearing evaluation by audiometry was done in all cases. All the data is collected, statistical analysis is done using SPSS program and documented for study. Results: One hundred patients with 119 perforated tympanic membrane, age ranged between 8 to 60 years, 44 males and 56 females were studied. Bilateral tympanic membrane perforation were seen in 19 patients, right sided perforation in 39 and left sided in 42 patients respectively. Large central perforation involving all four quadrants was the most common otologic findings seen in 72 ears (60.50%) whereas perforation in posterosuperior quadrant was the least common finding seen in 3 patients (2.52%). Significant relation is observed between site of perforation and degree of hearing loss; posterior placed perforations seem to have larger hearing loss. Ninety-five perforations (79.83%) showed more loss in low frequencies with larger air bone gap at low frequencies. The longer the duration of ear discharge, the more the hearing loss. Conclusion: The larger the perforation, the greater the decibel loss in sound perception. The location of perforation on the tympanic membrane and the duration of ear discharge have significant effect on the magnitude of hearing loss. Key words: chronic suppurative otitis media; tympanic membrane perforation; hearing loss DOI: 10.3126/kumj.v7i4.2761 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 397-401